Determination of Parameters of Asynchronous Electric Machines with Asymmetrical Windings of Electric Locomotives - Sergey Goolak; Juraj Gerlici; Viktor Tkachenko; Svitlana Sapronova; Tomas Lack; Kateryna Kravchenko (Communications - Scientific letters of the University of Zilina, 2019)
This article is devoted to development of a method for calculating the parameters of an asynchronous motor of an electric locomotive with asymmetrical windings of stator and rotor. A method for determining self and mutual inductances of the stator and rotor phases of an asynchronous motor with asymmetric windings and their relations to mechanical variables is proposed. It is based on comparing two equations of stored magnetic energy, one equation calculated through induction, magnetic field strength and geometrical dimensions and another equation calculated through the parameters of the motor circuits. It is shown that the obtained solutions correspond to the previously existing methods, but they give the additional possibilities in mathematical modeling. The proposed technical solution allows higher accuracy developing of a mathematical model of a drive with an asynchronous motor having asymmetrical stator and rotor windings for studying dynamic processes during the operation of the specified drive, in particular, the drive of auxiliary machines for electric locomotive, where an asynchronous motor with asymmetrical stator windings is used as a phase release.